2006
DOI: 10.1111/j.1365-263x.2006.00673.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental abscess in a tooth with intact dens evaginatus

Abstract: This article reports a case of dental abscess in a mandibular premolar with intact dens evaginatus. Dentists are advised to critically evaluate those teeth with dens evaginatus, both clinically and radiographically, before attempting prophylactic treatments. This is particularly important medicolegally in case the tooth develops symptoms shortly after the prophylactic treatment. Dentists practising in Western countries should also be aware of this dental anomaly because of the increasing global migration of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…29 Chen et al 30 reported a successful case of apexification in a DE premolar with necrotic pulp and blunderbuss apex in a 20-year-old patient, in which calcium hydroxide was used for 7 months. Cho 19 also reported successful apexification using calcium hydroxide for 2 years in a premolar with intact DE, pulp necrosis and open apex of a 9-year-old patient. The favorable clinical, radiographic and histological responses obtained with calcium hydroxide are attributed to the involvement of Ca 2+ and OHin several cellular and molecular mechanisms leading to regeneration of periapical connective tissues.…”
Section: Discussionmentioning
confidence: 97%
“…29 Chen et al 30 reported a successful case of apexification in a DE premolar with necrotic pulp and blunderbuss apex in a 20-year-old patient, in which calcium hydroxide was used for 7 months. Cho 19 also reported successful apexification using calcium hydroxide for 2 years in a premolar with intact DE, pulp necrosis and open apex of a 9-year-old patient. The favorable clinical, radiographic and histological responses obtained with calcium hydroxide are attributed to the involvement of Ca 2+ and OHin several cellular and molecular mechanisms leading to regeneration of periapical connective tissues.…”
Section: Discussionmentioning
confidence: 97%
“…the external surface, to prevent bacterial contamination of the DE. [13][14][15] In this case, pulp necrosis might have occurred by the buccal wearing.…”
Section: Introductionmentioning
confidence: 84%
“…The structural variations associated with this anatomical alteration make it difficult to perform conventional root canal treatment, leading these teeth to require new therapeutic procedures. Early diagnosis and treatment of DE are required to prevent complications, by sealing communications between the DE and the external surface, to prevent bacterial contamination of the DE . In this case, pulp necrosis might have occurred by the buccal wearing.…”
Section: Discussionmentioning
confidence: 99%
“…However, fracture or wear of the tubercle in teeth with dens evaginatus could lead to pulp necrosis, various prophylactic treatments have been suggested to treat before symptoms occur. 13 Therefore, the treatment of talon cusp implicates careful clinical decision. 15 The treatment choices include; application of resin to reinforce the tubercles, placement of prophylactic restorations, selective grinding of the tubercles, extraction and partial pulpotomy.…”
Section: Discussionmentioning
confidence: 99%
“…5 Dens evaginatus is also a developmental anomaly characterized by the presence a tubercle or an extra cusp on the surface of an affected tooth and is found most frequently in premolar teeth. [13][14][15] It consists of an outer layer of enamel, a core of dentin and may contain a slender extension of pulp horn and appears as a tubercle arising from the occlusal or lingual surface of the tooth. 3,14 Dens evaginatus and talon cusp are names for the same anomaly.…”
mentioning
confidence: 99%